Unanticipated favoured adsorption affinity of Th(iv) ions towards bidentate carboxylate functionalized carbon nanotubes (CNT–COOH) over tridentate diglycolamic acid functionalized CNT: density functional theoretical investigation1. Issue 97 (21st October 2015) - Deb, A. K. Singha; Ali, Sk. M.; Shenoy, K. T.
<x xml:space="preserve">Abstract</x> CNT–COOH has higher adsorption affinity for Th4+ in aqueous solution compared to CNT–DGA, whereas pristine CNT has nil.